Modeling and vulnerability analysis of military communication network based on complex network - GUO Haoming; WANG Shuangling; YAN Xuefeng; ZHANG Kecheng (Xibei Gongye Daxue Xuebao)
Aiming at the complexity of military communication system and the characteristics of network structure, based on the complex network theory, the relay communication entity (node) is introduced, and the communication relationship between equipment entities is analyzed, the military communication network structure model is constructed. On this basis, the vulnerability of military communication network is analyzed from two perspectives: the network probability reconstruction model and the cascading failure propagation model based on node attributes. In addition, the evaluation index of military communication network vulnerability is given. Finally, the effectiveness of the proposed model method is verified by simulation experiments, which provides a theoretical basis for the analysis and construction of military communication network.